The target effect: Visual memory for unnamed search targets. Issue 11 (November 2014) - Thomas, Mark D.; Williams, Carrick C.
Search targets are typically remembered much better than other objects even when they are viewed for less time. However, targets have two advantages that other objects in search displays do not have: They are identified categorically before the search, and finding them represents the goal of the search task. The current research investigated the contributions of both of these types of information to the long-term visual memory representations of search targets. Participants completed either a predefined search or a unique-object search in which targets were not defined with specific categorical labels before searching. Subsequent memory results indicated that search target memory was better than distractor memory even following ambiguously defined searches and when the distractors were viewed significantly longer. Superior target memory appears to result from a qualitatively different representation from those of distractor objects, indicating that decision processes influence visual memory.